Location and size of the shallow magma reservoir beneath Kīlauea caldera, constraints from near‐source Vp/Vs ratios. Issue 20 (24th October 2015) - Lin, Guoqing; Amelung, Falk; Shearer, Peter M.; Okubo, Paul G.
Abstract: We present high‐resolution compressional wave to shear wave velocity ratios ( V p / V s ) beneath Kīlauea's summit caldera by applying an in situ estimation method using waveform cross‐correlation data for three similar earthquake clusters. We observe high V p / V s ratios (1.832 and 1.852) for two event clusters surrounded by the low background V p / V s value of 1.412 at ∼2.1 km depth below the surface. These high and low V p / V s ratios can be explained by melt‐ and CO2 ‐filled cracks, respectively, based on a theoretical crack model. The event cluster with the highest V p / V s ratio consists of long‐period events that followed the 1997 East Rift Zone eruption, indicating their association with fluid and magma movement. The depths of the two clusters with high V p / V s ratios are consistent with the magma reservoir location inferred from geodetic observations. Their locations east and north of Halema'uma'u crater suggest a horizontal extent of a few kilometers for the reservoir. Key Points: Low in situ Vp/Vs ratio dominating the summit caldera High in situ Vp/Vs ratios observed east and north of Halema'uma'u crater The anomalous features can be explained by theoretical modeling and consistent with other data